The in vitro and in vivo Antioxidant and Immunomodulatory Activity of Incomplete Degradation Products of Hemicellulosic Polysaccharide (Galactomannan) From Sesbania cannabina - Tao, Yuheng; Wang, Ting; Lai, Chenhuan; Ling, Zhe; Zhou, Yanmin; Yong, Qiang (Frontiers in Bioengineering and Biotechnology, 2021)
As known, the nutritional status affects antioxidant capacity and immunity, ultimately affecting the body’s health. Recently, hemicellulosic polysaccharides of galactomannan in different biomass and their degradation products are gaining more attention due to excellent antioxidant enhancement and immunomodulatory activity. Herein, incomplete degradation products of galactomannan (IDPG) were prepared from the enzymatic hydrolysis of Sesbania cannabina seeds, followed by the in vitro and in vivo experiments. Using an H2O2-injured RAW264.7 cells model, IDPG was demonstrated to have antioxidant capacity, as indicated by superoxide dismutase (SOD) activity and malondialdehyde (MDA) content. While in the evaluation in laying hens (68-weeks-old), diets were supplemented with 0, 0.01%, 0.025%, and 0.05% IDPG for 8 weeks, respectively. Our results showed that IDPG can improve antioxidant capacity by increasing antioxidants contents and reducing MDA content. Furthermore, IDPG can increase immunoglobulins and cytokines secretion, thereby enhancing the immunity of laying hens. This result was further demonstrated by in vitro experiment, in which IDPG significantly increased the secretion of nitric oxide (NO), tumor necrosis factor-α (TNF-α), interleukin 6 (IL-6), and toll-like receptor 4 (TLR4) in RAW264.7 cells (P < 0.05). Overall, IDPG can improve antioxidant function and modulate immunological response, thereby the concept of using IDPG for health may gain a little more credibility.